Nanocellulose‑based materials and recent application for heavy metal removal - Haziqatulhanis, Ibrahim; Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail (Springer Nature, 2021)
Among numerous sustainable advanced nanomaterials, nanocellulose is receiving increasing attention for its utilization in water treatment technologies due to its various specific properties and functionalities. The term “nanocellulose” is used for cellulosic material having a nanoscopic scale (or nanoscale) for their dimensional characteristics. It can be obtained in three different forms, which are fibrous form, crystalline form, or bacterial form. One of the benefits of this natural polymer is that it can be found abundantly on Earth, as most plants or waste contains the cellulose. For decades, this material has been widely used in various applications, mainly in water purification, with current studies focusing on surface functionalization of nanocellulose to enhance its properties. This brief review aims to provide the readers with the recent studies (year 2015 to year 2021) of nanocellulose properties, alongside the application of the material for removal of heavy metals from water and its reusability efficiency. In this regard, the main limitations for the specific applications of nanocellulose-based materials and its future prospective are identified in an effort to make possible enhancements in the future.